PEMANFAATAN PASIR SILIKA SEBAGAI BAHAN PENGGANTI WATER GLASS PADA PEMBUATAN BETON GEOPOLIMER - Elmar D, M Dodi; Firdaus, Firdaus (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
As time goes by in the Indonesian construction sector, concrete is widely used to build infrastructure such as buildings, roads, dams, bridges and so on.Concrete is a mixture formed by fine aggregate, coarse aggregate in the form of crushed stone or gravel mixed together with a paste made from cement and water. To produce certain characteristics, one or more chemicals are usually added to increase the hardening time. Therefore, good quality concrete depends on the mixture. The mixture that is very necessary in making concrete is cement. The use of cement in the construction sector causes an increase in portland cement production which has a negative impact on the environment. This is because the process of burning raw materials to produce cement produces CO2 directly into the air. Therefore, other alternative materials are needed that can replace cement, namely by utilizing the development of concrete using a binder known as geopolymer.Geopolymer is a concrete mixture in which the use of Portland cement as a binding paste is replaced with other materials such as fly ash or fly ash left over from burning coal. Geopolymer is an environmentally friendly material that was developed as an alternative to cement concrete. Geopolymers are also new materials used for coatings, adhesives, new binders for fiber composites and new cements for concrete. The main ingredient for making geopolymer concrete is a material that contains a lot of aluminum and silica. These substances are found in many industrial waste materials such as those contained in fly ash or fly ash. Keywords: compressive strength of geopolymer concrete